Epidemiological Characteristics and Family Relatives among Thalassemic Patients in Sulaimani City, Kurdistan Region, Iraq - Kamal Jalal Rashid (Kurdistan Journal of Applied Research)
Thalassemia is a well-known inherited hematologic disorder caused by a decrease or an absence of globin production. Patients with thalassemia suffer from chronic hemolytic anemia and its sequelae. A descriptive study was undertaken in Sulaimani Thalassemia and Congenital Blood Disease Center. The self-administered questionnaire was used to 140 patients who had thalassemia and visited to the hospital during the study periods to assess the patients’ characteristics and parent’s relative’s relation to thalassemic patients.  Data were entered into spreadsheets and analyzed in Statistical Package for Social Sciences (SPSS) version 22. Descriptive analysis was performed and frequencies and percentages were reported. Associations between categorical variables were checked using Chi-squared test. Out of 140 patients 50.0% of patients were males and 50.0% were female; the mean age was 12.8 years-old. The most frequent thalassemic patents were come from rural area 95.0%. Majority of patients have major type of thalassemia 84.3%. Most of the patients cannot continue to the study accounted 66.4%. About number of children most of the patient’s family had more than 3 children 99.3%. Majority of patient’s parents is carrier for thalassemia and accounted with 90 (65.0%), from those patients with major thalassemia are 77 (85.6) and few cases with minor thalassemia 4 (4.4%). These relations are statistically significant at (p<0.05). Majority of patients who have major type of thalassemia were from rural area followed by urban area 113 (95.8%) vs. 7 (5.0%), these differences are statistically significant at (p?0.01), from major types of thalassemic patients; 85 (94.4%) of them were both father and mother are carrier of thalassemia. Statistically significant relation was found at (p<0.05). In conclusion, thalassemia is an important cause of morbidity among thalassemic patients. In our community, thalassemia is more frequent in rural population. Therefore, it is a crucial for monitoring and examination of those who are carriers. Moreover, the lack of health education on thalassemia was the major problems related with awareness of families.